STOPE STABILITY ANALYSIS AT UNDERGROUND GOLD VEIN MINING PT XYZ - Athhar F. P., Muhammad
Instability in underground mining can arise from large opening dimensions, impacting not only safety but also economic aspects. Stability studies of mining openings are conducted by companies to maximize the dimensions of mining operations. This study applies numerical methods to analyse the mine opening in underground cut and fill gold mine. A total of four mining scenarios are formed to illustrate mining sequences and a support analysis is conducted to obtain the stability of the mine opening. Total displacement, yielded elements, and support capacity plot are used as stability indicators in each scenario. Through the interpretation of the total displacement, the deformation reduction is obtained in each mining scenario. Meanwhile, through the yielded element it can be seen that the majority of opening scenarios experience a reduction in collapse height in each scenario except for the 3rd scenario where there is additional collapse on the left wall. Then, by analysing the support capacity plot it is proven that each scenario is in a stable state with the recommended types of reinforcement and rock bolt, shotcrete, wire mesh, steel set, and wooden supports according to the characteristics of each scenario.